Method for regenerating activity of inactivated metal catalytic electrode

Electrochemical treatment of the inactivated catalytic electrode through cyclic voltammetry or pulsed redox method solves the problem of reduced catalyst activity, significantly improves current density and Faraday efficiency, extends the service life of the electrocatalyst, and achieves high efficiency and environmental protection catalyst regeneration and recycling.

CN119221013APending Publication Date: 2024-12-31GUILIN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411518708.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the electrocatalysis process, changes in the structure and composition of the catalyst surface lead to a reduction in catalytic activity. How to extend the service life of the catalyst and maintain long-term reaction activity and stability is a hot topic.

Method used

The inactivated metal catalytic electrode is subjected to electrochemical redox treatment by cyclic voltammetry reduction method or pulsed redox method to restore its activity. Specific methods include cyclic voltammetry reduction method for nanoporous Au-Ag alloy electrodes, pulsed redox and electrolytic reduction method for nanoporous Ag electrodes, and regulating the surface structure and porous layer thickness of the electrodes to change the degree of catalytic activity recovery.

Benefits of technology

It significantly improves the current density and Faraday efficiency of the catalytic electrode, extends the service life of the catalytic electrode in long-term reactions, reduces the demand for precious metal catalytic materials, reduces the generation of waste catalysts, improves recycling efficiency, and is in the electrical field. Efficient and environmentally friendly catalyst regeneration is achieved in the chemical environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221013A_ABST
    Figure CN119221013A_ABST
Patent Text Reader

Abstract

The invention provides a method for regenerating the activity of an inactivated metal catalytic electrode, and belongs to the technical field of electrode regeneration. The method comprises the following steps: performing electrochemical oxidation-reduction treatment on an inactivated metal catalytic electrode to obtain an active regenerated metal catalytic electrode; the electrochemical oxidation reduction treatment comprises a cyclic voltammetry reduction method or a method for electrolytic reduction after pulse oxidation reduction. According to the method, the activity of the inactivated metal catalytic electrode is regenerated by adopting a cyclic voltammetry reduction method or an electrolytic reduction method after pulse oxidation reduction, so that the service life of the metal catalytic electrode in long-time reaction can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode regeneration technology, and in particular to a method for regenerating the activity of a deactivated metal catalytic electrode, and more particularly to a method for regenerating the activity of a deactivated catalytic electrode based on an electrochemical redox technology. Background Art

[0002] Electrocatalysis is a catalytic reaction that accelerates the charge transfer reaction at the interface of electrodes and electrolytes. It can use electrical energy to convert usable chemical substances on the electrode surface. It is widely used in water electrolysis, fuel cells, and electrochemical CO2 reduction (ECR) because of its green, environmentally friendly, and sustainable characteristics. Electrode materials are both catalysts for electrochemical reactions and the place where electrode reactions take place. Therefore, their surface structure is the key to determining the performance of electrocatalytic reactions. Nanoporous metals have high porosity, high specific surface area, and excellent conductivity. In addition, the pore structure provides a fast ion transport channel, making them very promising electrode materials.

[0003] However, during long-term electrocatalysis, the structure and composition of the catalyst surface often undergo dynamic changes due to surface reconstruction, resulting in reduced catalytic activity. How to extend the service life of the catalyst so that the catalyst can maintain long-term reaction activity and stability is a hot issue in the field of electrocatalysis. Therefore, it is of great significance to activate and regenerate the activity of the deactivated electrode after long-term reaction.

[0004] Therefore, there is an urgent need to develop a method to regenerate the activity of deactivated catalytic electrodes and extend the life of electrocatalysts in long-term catalytic reactions. Summary of the invention

[0005] In view of this, in order to solve the technical problem that the catalytic activity of existing catalysts is reduced and affects the service life, the present invention provides a method for regenerating the activity of deactivated metal catalytic electrodes. The activity of the deactivated metal catalytic electrodes is regenerated by adopting a cyclic voltammetric reduction method or a pulse oxidation-reduction method followed by an electrolytic reduction method, which can effectively extend the service life of the catalytic electrode in long-term reactions.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for regenerating the activity of a deactivated metal catalytic electrode, wherein the deactivated metal catalytic electrode is subjected to electrochemical oxidation-reduction treatment to obtain an active regenerated metal catalytic electrode;

[0008] The electrochemical redox treatment includes a cyclic voltammetric reduction method or a pulse redox followed by an electrolytic reduction method.

[0009] Preferably, when the metal catalytic electrode is a nanoporous Au-Ag alloy electrode, a cyclic voltammetric reduction method is used.

[0010] Preferably, in the cyclic voltammetry reduction method, the cyclic voltammetry method is first used for testing, and the potential window in the cyclic voltammetry method is set to a starting potential of 0.74 V vs. RHE, a termination potential of 1.74 V vs. RHE, and a scan rate of 5 mV s -1 , scanning circle number ≥ 10 circles, completion time 4000s;

[0011] Then, the Au-Ag alloy electrode is subjected to electrochemical CO2 reduction using a current-time method.

[0012] Preferably, the potential of the current-time method is selected to be -0.5 V vs. RHE.

[0013] Preferably, when the metal catalytic electrode is a nanoporous Ag electrode, a pulse oxidation-reduction followed by electrolytic reduction method is adopted.

[0014] Preferably, in the pulse oxidation-reduction followed by electrolytic reduction method, a multi-potential step method is first used to perform electrochemical oxidation to obtain an Ag electrode; and then a current-time method is used to perform electrochemical CO2 reduction on the obtained Ag oxide electrode.

[0015] Preferably, the parameters of the multi-potential step method are set to E1(V)=0.8Vvs.RHE, T1(s)=0.01; E2(V)=2.2V vs.RHE, T2(s)=0.01, and the number of cycles is 360000 cycles; the potential of the current-time method is set to -0.8V vs.RHE, and the time is 900s.

[0016] Preferably, the Au-Ag alloy electrode refers to Au 35 Ag 65 The loose porous material is prepared by the alloy strip being dealloyed or electrochemically corroded by concentrated nitric acid.

[0017] Preferably, the Au 35 Ag 65 In the alloy strip, the atomic percentage content of Ag is 2.5 at.% to 5 at.%.

[0018] Preferably, the nanoporous Ag electrode refers to a porous material prepared by electrochemical oxidation and reduction of Ag foil.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses cyclic voltammetric reduction or pulse redox treatment to effectively restore and regenerate the activity of metal catalytic electrodes whose performance has been reduced after a long period of reaction, and both the current density and the Faraday efficiency are significantly improved.

[0021] (2) The present invention can be widely used in catalytic electrodes composed of nanoporous metal alloys or nanoporous metal elements, and can effectively extend the service life of the catalytic electrode in long-term reactions. The treatment method is simple and efficient, environmentally friendly, and can be repeated in an electrochemical environment, thereby reducing production costs and environmental impacts.

[0022] (3) The nanoporous Au-Ag electrode reactivated by the electrochemical redox technology of the present invention can reduce CO2 to CO with a catalytic selectivity of 90% in a CO2-saturated 0.5M KHCO3 electrolyte and a potential of -0.5V vs.RHE; the nanoporous Ag electrode can reduce CO2 to CO with a catalytic selectivity of 85% in a CO2-saturated 0.1M KHCO3 electrolyte and a potential of -0.8V vs.RHE, and the current density of the nanoporous Ag electrode increases from 1.78mA cm -2 Increased to 4.61 mA cm -2 ,It can be seen that the present invention can effectively restore the activity of the deactivated catalytic electrode.

[0023] (4) The present invention can regulate the surface structure of the catalytic electrode, including the crystal surface ratio and the thickness of the porous layer, by controlling the time of the cyclic voltammetric reduction method or the time of the pulse redox method, thereby changing the degree of catalytic activity recovery.

[0024] (5) The present invention can significantly reduce the demand for precious metal catalytic materials, thereby reducing material costs. At the same time, the generation of waste catalysts can be reduced through the regeneration and reuse of catalysts, which helps to improve the recycling efficiency of catalysts and further promote sustainable development and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The schematic diagram of the electrochemical redox technology used in the embodiment of the present invention to regenerate the activity of the deactivated catalytic electrode is shown in (a) cyclic voltammetry of the nanoporous Au electrode; (b) electrolytic reduction method followed by pulse redox of the nanoporous Ag electrode;

[0026] Figure 2 The surface morphology SEM photos of the nanoporous Au electrode in different catalytic stages and the voltammetric curves measured by Pb underpotential deposition in Example 1 of the present invention, (a, d) NPG-1 in the prepared state of the sample; (b, e) after a long-term catalytic reaction for 10 hours; (c, f) after reactivation;

[0027] Figure 3is the percentage of crystal faces of the nanoporous Au electrode in Example 1 of the present invention at different catalytic stages;

[0028] Figure 4 The cross-sectional SEM photos of the nanoporous Ag electrode in Example 2 of the present invention at different catalytic stages, (a) sample preparation state NPS-1; (b) after long-term catalytic reaction for 12 hours; (c) after reactivation;

[0029] Figure 5 : is the variation trend of the electrocatalytic CO2 reduction current density and the Faraday efficiency of generating CO over time, and the circle indicates the Faraday efficiency of generating CO by the catalytic electrode after reactivation; wherein, (a) is the nanoporous Au electrode of Example 1 of the present invention; (b) is the nanoporous Ag electrode of Example 2;

[0030] Figure 6 Schematic diagram of the changes in the electrode surface structure in different catalytic stages; wherein (a) is the nanoporous Au electrode in Example 1 of the present invention; and (b) is the nanoporous Ag electrode in Example 2.

[0031] Figure 7 Figure 1 shows the trend of current density and Faraday efficiency of CO generation in the nanoporous Au electrode in comparative example 1 in 0.5M KHCO3 solution purified by EDTA at -0.5V vs. RHE. The circle shows the Faraday efficiency of CO generation by the catalytic electrode after reactivation; (b) the voltammogram of Pb underpotential deposition measurement; (c) the percentage of crystal faces of the nanoporous Au electrode at different catalytic stages after 10 hours of reaction in unpurified and EDTA-purified 0.5M KHCO3 solution; (d) CV cyclic voltammogram of the nanoporous Au electrode before and after 10 hours of catalytic reaction in 0.5M KHCO3 solution purified by EDTA. DETAILED DESCRIPTION

[0032] The present invention provides a method for regenerating the activity of a deactivated metal catalytic electrode, wherein the deactivated metal catalytic electrode is subjected to electrochemical oxidation-reduction treatment to obtain an active regenerated metal catalytic electrode;

[0033] The electrochemical redox treatment includes a cyclic voltammetric reduction method or a pulse redox followed by an electrolytic reduction method.

[0034] In the present invention, the metal catalytic electrode is a nanoporous Au-Ag alloy electrode or a nanoporous Ag electrode, and the catalytic activity is significantly reduced after a long period of electrochemical catalytic reaction.

[0035] Nanoporous Au-Ag alloy electrodes or nanoporous Ag electrodes have a higher specific surface area and generally exhibit porous characteristics, with pore sizes ranging from tens of nanometers to micrometers.

[0036] In the present invention, the nanoporous Au-Ag alloy electrode refers to Au 35 Ag 65 The alloy strip is subjected to concentrated nitric acid dealloying corrosion or electrochemical corrosion for preferably 8 hours to obtain a surface loose porous material, wherein the Ag atomic percentage content is preferably 2.5at.% to 5at.%. Due to the low Ag element content, it is academically referred to as nanoporous Au (nanoporous gold, NPG); nanoporous Ag (nanoporous silver, NPS) electrode refers to a porous material prepared by electrochemical oxidation and reduction of a metal single substance Ag foil.

[0037] In the present invention, when the metal catalytic electrode is a nanoporous Au-Ag alloy electrode, a cyclic voltammetric reduction method is used.

[0038] In the present invention, in the cyclic voltammetry reduction method, the cyclic voltammetry method is first used for testing, and the potential window in the cyclic voltammetry method is preferably set to a starting potential of 0.74 V vs. RHE, a termination potential of 1.74 V vs. RHE, and a scan rate of 5 mV s -1 , the number of scanning circles is preferably ≥10, and the completion time is 4000s;

[0039] Then, the Au-Ag alloy electrode is subjected to electrochemical CO2 reduction using a current-time method.

[0040] Specifically, it can be:

[0041] The nanoporous Au-Ag alloy electrode was cleaned with deionized water and used as a working electrode. The two chambers of the H-type electrolytic cell were separated by a Nafion-115 membrane, and 30 mL of 0.1 M H2SO4 solution was added. A platinum mesh was used as a counter electrode, and a Hg / Hg2SO4 electrode was used as a reference electrode. The test was performed by cyclic voltammetry, and the potential window was set to a starting potential of 0.74 V vs. RHE, a termination potential of 1.74 V vs. RHE, a scan rate of 5 mV s-1, and a scan number of 10 circles to improve the activity recovery degree of the inactivated electrode. The completion time was 4000 s. The surface structure of the nanoporous Au electrode can be regulated by controlling the scan number of the cyclic voltammetry reduction method.

[0042] In an H-type electrolytic cell of a CO2-saturated 0.5M KHCO3 electrolyte solution, reactivated nanoporous Au was used as the working electrode, a platinum mesh was used as the counter electrode, and a calomel electrode was used as the reference electrode. The current-time method was used with a potential selection of -0.5V vs.RHE for electrochemical CO2 reduction. The electrochemical working test current I and current density j=current I / electrode surface area S were used. The Faraday efficiency was calculated using the product concentration obtained by gas chromatography. Each test lasted 30 minutes.

[0043] In the present invention, when the metal catalytic electrode is a nanoporous Ag electrode, a pulse oxidation-reduction followed by electrolytic reduction method is adopted.

[0044] In the present invention, in the pulse oxidation-reduction followed by electrolytic reduction method, a multi-potential step method is first used to perform electrochemical oxidation to obtain an Ag electrode; and then a current-time method is used to perform electrochemical CO2 reduction on the obtained Ag oxide electrode.

[0045] Specifically, it can be:

[0046] The nanoporous Ag electrode was cleaned with deionized water and used as a working electrode. The two chambers of the H-type electrolytic cell were separated by a Nafion-115 membrane, and 30 mL of 0.2 M NaOH solution was added. A platinum mesh was used as a counter electrode, and an Ag / AgCl electrode was used as a reference electrode. The Ag oxide electrode was first electrochemically oxidized by a multi-potential step method. The parameters were set to E1 (V) = 0.8 V vs. RHE, T1 (s) = 0.01; E2 (V) = 2.2 V vs. RHE, T2 (s) = 0.01, the number of cycles was 360000 cycles, and the electrochemical oxidation time was preferably 2 hours to improve the activity recovery of the inactivated electrode. Then the solution was changed to CO2-saturated 0.1 M KHCO3, and the obtained Ag oxide electrode was electrochemically reduced by CO2 using the current-time method. The potential was preferably set to -0.8 V vs. RHE, and the treatment time was 900 s. The thickness of the porous layer of the nanoporous Ag electrode can be regulated by controlling the pulse redox time.

[0047] The technical solution of the present invention is described clearly and in detail below in conjunction with specific embodiments.

[0048] Example 1

[0049] The method for regenerating the activity of an inactivated nanoporous Au-Ag alloy electrode by electrochemical oxidation-reduction comprises the following steps:

[0050] S1, the inactivated nanoporous Au electrode was cleaned with deionized water, and used as the working electrode after soaking for about 5 minutes. The two chambers of the H-type electrolytic cell were separated by a Nafion-115 membrane, and 30 mL of 0.1 M H2SO4 solution was added. The platinum mesh was used as the counter electrode, and the Hg / Hg2SO4 electrode was used as the reference electrode;

[0051] The Au-Ag alloy electrode in S1 of Example 1 is made of high-purity Au (purity 99.99%), which is obtained by high vacuum arc melting-rolling to obtain an Au electrode with a thickness of about 25 μm. 35 Ag 65 The alloy strip is then subjected to concentrated nitric acid (69%) dealloying corrosion or electrochemical corrosion for 8 hours to obtain a deactivated electrode in which the Ag atomic percentage content is 2.5at.% to 5at.%, and the activity is significantly reduced after long-term CO2 electrochemical catalysis.

[0052] S2 was tested by cyclic voltammetry with the potential window set to a starting potential of 0.74 V vs. RHE, an ending potential of 1.74 V vs. RHE, and a scan rate of 5 mV s -1 , the number of scanning circles is set to 10, and the completion time is 4000s;

[0053] S3, in an H-type electrolytic cell of a CO2-saturated 0.5M KHCO3 electrolyte solution, with reactivated nanoporous Au as the working electrode, a platinum mesh as the counter electrode, and a calomel electrode as the reference electrode, the current-time method was adopted, and the potential was selected as -0.5V vs.RHE. Electrochemical CO2 reduction was carried out, with the electrochemical working test current I, current density j = current I / electrode surface area S, and the Faraday efficiency was calculated using the product concentration obtained by gas chromatography. Each test lasted 30 minutes.

[0054] In Example 1, a cyclic voltammetry (CV) test was performed using a three-electrode method in an H-type electrolytic cell. The test results are shown in FIG. Figure 1 As shown in (a), starting from the second cycle, there are two oxidation peaks at 1.39V and 1.56V vs.RHE, corresponding to the oxidation peaks of Au, and a large reduction peak at 1.12V vs.RHE. Compared with the first cycle, the peak shape changes of CV from the second to the tenth cycle are very small, indicating that the surface structure is mainly repaired.

[0055] In Example 1, in order to illustrate the changes in the surface structure of nanoporous Au, scanning electron microscopy and lead underpotential deposition were used for characterization. Figure 2 (a) shows the prepared state of the nanoporous Au sample. After 10 hours of CO2 electrochemical reduction test (as shown in Figure 2In (b), there is obvious ligament coarsening and pore blockage, similar to the phenomenon of "sintering". After 10 cycles of cyclic voltammetry test and reactivation, the porous structure on the surface shows signs of recovery ( Figure 2 c).

[0056] Since the oxidation peak potential of lead underpotential deposition (Pb-upd) is closely related to the crystal plane structure of the Au electrode surface, the proportion of different crystal planes on the porous gold electrode surface can be accurately calculated by the area of ​​the oxidation peak after Pb-upd. The CV oxidation peak of Pb-upd has three desorption peaks at different potentials: the first small peak is around 0.32V, and according to the literature, this peak corresponds to the surface step; the second strong peak is around 0.45V, corresponding to the {111} crystal plane; the third broad peak is around 0.61V, which can be divided into two peaks, one is 0.56V corresponding to the {100} crystal plane, and the other is 0.62V corresponding to the {110} crystal plane. Most of the surface steps are high-index crystal planes with a large number of low-coordinated surface atoms, so they have been considered to be the source of high catalytic activity of nanoporous metals.

[0057] Pb-upd was carried out in a three-electrode H-type electrolytic cell with a solution of 0.1 M NaOH + 10 -3 M Pb(NO3)2, N2 was passed through for 30 minutes to remove oxygen before testing. The reference electrode was Hg / HgO (1M KOH, TJ Aida R0501). Cyclic voltammetry was used for testing, with the potential window set to a starting potential of 0.13 V vs. RHE, a termination potential of 0.87 V vs. RHE, and a scan rate of 5 mV S -1 Since the porous electrode has a small pore size and a large surface curvature, multiple measurements are required until the two measured curves coincide to obtain a true data curve. Peak separation and peak shape fitting can be achieved through the peak anlalyzer module in the Origin software. The proportion of different crystal faces can be calculated from the peak area, such as Figure 2 d~f show the voltammograms obtained from the Pb underpotential deposition measurements in the prepared state, after 10 hours of CO2 electrochemical reduction reaction, and after reactivation, respectively.

[0058] The proportion of different crystal faces can be obtained by calculating the peak area, such as Figure 3As shown in the figure. In the prepared state (NPG-1), the proportion of surface steps is about 29.8%; after 10 hours of reaction, the proportion of surface steps drops rapidly from 29.8% to 14.8%, resulting in a significant reduction in the number of active sites; when the electrode that has been inactivated after a long reaction is reactivated by potential cycling (Re-cv), it can be seen that the proportion of surface steps has recovered to 27.6%, indicating that the number of catalytic active sites has recovered to the level of the prepared state.

[0059] In Example 1, the active regenerated nano-Au electrode was subjected to a CO2 electrochemical reduction test. Figure 5 As shown in (a), the deactivated electrode reacted at -0.5 V vs. RHE for 10 hours. Although the current density did not change significantly, the Faradaic efficiency of CO generation decreased from 98% to about 80%. After reactivation using the cyclic voltammetric reduction method, it returned to above 90% (as shown by the circle in the upper right corner) and lasted for more than two hours, indicating that the activity of the deactivated catalytic electrode was regenerated.

[0060] Example 2

[0061] A method for regenerating the activity of a deactivated nanoporous Ag (nanoporous silver, NPS) catalytic electrode by electrochemical redox, comprising the following steps:

[0062] S1, the inactivated nanoporous Ag electrode was cleaned with deionized water, and used as the working electrode after soaking for about 5 minutes. The two chambers of the H-type electrolytic cell were separated by a Nafion-115 membrane, and 30 mL of 0.2 M NaOH solution was added. The platinum mesh was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode;

[0063] S2, the Ag oxide electrode was first obtained by electrochemical oxidation using the multi-potential step method, the parameters were set to E1(V) = 0.8V vs.RHE, T1(s) = 0.01, E2(V) = 2.2V vs.RHE, T2(s) = 0.01, the number of cycles was 360000 cycles, and the electrochemical oxidation time was 2 hours; then the solution was changed to 0.1MKHCO3 saturated with CO2, and the obtained Ag oxide electrode was electrochemically reduced with CO2 using the current-time method, the potential was set to -0.8V vs.RHE, and the treatment time was 900s. Figure 1 (b) as shown.

[0064] S3, in an H-type electrolytic cell of a CO2-saturated 0.1M KHCO3 electrolyte solution, with reactivated nanoporous Ag as the working electrode, a platinum mesh as the counter electrode, and an Ag / AgCl electrode as the reference electrode, the current-time method was adopted, and the potential was selected as -0.8V vs.RHE, for electrochemical CO2 reduction. The electrochemical working test current I, current density j = current I / electrode surface area S, was used to calculate the Faraday efficiency using the product concentration obtained by gas chromatography test. Each test lasted 30 minutes.

[0065] In S1 of Example 2, the nanoporous Ag electrode is a strip with a thickness of about 50 μm obtained by rolling high-purity Ag (purity 99.99%), which is obtained by pulse oxidation-reduction for 5 hours and then electrochemical CO2 reduction for 30 minutes, and after long-term CO2 electrochemical catalysis, the activity of the deactivated electrode is significantly reduced.

[0066] In Example 2, after the pulse oxidation-reduction and electrochemical CO2 reduction in steps S1 and S2, the cross section of the sample was observed using a scanning electron microscope. Figure 4 As shown. After 12 hours of electrocatalytic CO2 reaction, the thickness of the porous layer decreased from 8.7 μm in the prepared state (NPS-1) to 7.2 μm (NPS-2), while after reactivation, the thickness of the porous layer increased to 13.2 μm (NPS-3), and a hierarchical multi-level porous structure was formed, which would increase its electrochemical active area and active sites.

[0067] In Example 2, the active regenerated nano-Ag electrode was subjected to a CO2 electrochemical reduction test. Figure 5 As shown in b, the Faradaic efficiency of CO generation at the deactivated electrode at -0.8 V vs. RHE is about 69%, and after reactivation it returns to ~85%, and the current density also increases from 1.78 to 4.61 mA cm -2 , and the activity can last for more than two hours without decay, indicating that the activity of the inactivated catalytic electrode has been regenerated.

[0068] In Example 2, Figure 6The schematic diagrams of the changes in the surface structure of the nanoporous Au electrode (a) and the nanoporous Ag electrode (b) at different catalytic stages are summarized; for the nanoporous Au electrode, after 10 hours of electrocatalytic CO2 reduction (ECR) reaction, the main structural change compared to the prepared state is the decrease in the proportion of surface steps, resulting in a decrease in the number of catalytic active sites. After reactivation by cyclic voltammetry, the proportion of surface steps will increase again, thereby restoring and regenerating the catalytic activity; for the nanoporous Ag electrode, after 12 hours of electrocatalytic CO2 reduction reaction, the main structural change is the decrease in the thickness of the porous layer, resulting in a decrease in the electrochemical active area. After pulse redox and electrolytic reduction, a layered multi-level porous structure is formed, and the thickness of the porous layer is significantly increased, resulting in an increase in its electrochemical active area and active sites, thereby restoring and regenerating the catalytic activity.

[0069] In summary, the present invention can regenerate the activity of the catalytic electrode that has been deactivated after a long reaction by electrochemical redox technology, and the current density and the Faraday efficiency of the target product will be significantly improved, thereby extending the life of the electrocatalyst in a long catalytic reaction. By controlling the time of the cyclic voltammetric reduction method (or the number of turns) or the time of the pulse redox method (or the number of turns), the surface structure and the thickness of the porous layer of the catalytic electrode can be regulated, thereby changing the degree of recovery of the catalytic activity. The present invention can significantly reduce the demand for precious metal catalytic materials and improve the recycling efficiency of the catalyst.

[0070] Comparative Example 1

[0071] One reason for the change in the surface structure of the catalytic electrode during the long-term electrochemical reduction of CO2 is the deposition of trace metal ions in the solution. Common metal ions such as Zn, Pb, and Cu are reduced to a metallic state and deposited on the electrode surface at the reduction potential. The most common method in the prior art is to use a chelating agent EDTA (ethylenediaminetetraacetic acid) to complex these heavy metal ions, thereby achieving the purpose of purifying the solution and inhibiting the deposition of metal ion impurities on the surface of the catalytic electrode.

[0072] In order to compare the effects of EDTA purification solution and the two techniques of the present invention, Figure 7 As shown in the figure, 17μM EDTA (Aldrich, 99.995%) was added to the 0.5MKHCO3 solution for purification, and then a long-term CO2 electrocatalytic test was carried out in this purified solution. It can be found that the catalytic activity also decreases in the EDTA-purified solution, but the downward trend is slower than that in the unpurified solution ( Figure 5a) is significantly smaller. After 10 hours of catalytic reaction, the FE of generated CO dropped from 96% to 84%, and it could be maintained above 90% before 8 hours, but the catalytic performance dropped significantly after 8 hours. This shows that EDTA purification of the solution can extend the life of the catalytic electrode to a certain extent in the initial stage and reduce the trend of its activity decline, but it is not suitable for longer electrochemical catalytic reactions (more than 10 hours). Pb underpotential deposition test results ( Figure 7 b, 7c) confirmed that the surface step ratio in the EDTA-purified solution was reduced by 6.9% (from 29.8% to 22.9%) compared with that before the catalytic reaction, while it was reduced by 15% (from 29.8% to 14.8%) in the unpurified solution, indicating that the EDTA-purified solution has a certain effect on inhibiting the deposition of metal ion impurities in the solution and catalyzing the changes in the surface structure of the electrode. Comparison of the CV of the NPG electrode before the catalytic reaction in the EDTA-purified 0.5M KHCO3 solution and after 10 hours of reaction ( Figure 7 d), it can be found that the oxidation peak of Zn is no longer observed, and the oxidation peak of Pb has also become very small, but the oxidation peak of Cu still exists. This shows that the EDTA purification solution can effectively remove impurities such as Zn and Pb in the solution, but the effect of removing Cu ion impurities is not obvious, which causes the NPG electrode to be deactivated after a longer catalytic reaction. Using the method in Example 1 of the present invention, the deactivated electrode is regenerated, and it can be found that its FE for generating CO increases from 84% to 93%, as shown in FIG. Figure 7 The oval circle in a shows that the method for regenerating the activity of the deactivated metal catalytic electrode in the present invention has a more significant effect than the purification solution method.

[0073] As an organic compound, EDTA may pollute soil and water bodies and be toxic to organisms if it leaks during use. In addition, it may accumulate in the environment and cause ecological damage. The reagents and materials used in the present invention are more environmentally friendly, and the treatment method is simple and efficient, environmentally friendly, and can be repeated in an electrochemical environment, significantly reducing production costs and negative impacts on the environment.

[0074] Comparative Example 2

[0075] After inquiry, it was found that there is another invention patent that is related to the present application patent. Invention name: An in-situ regeneration method for electrochemical reduction of CO2 catalytic electrode, publication number CN118048662A. The in-situ regeneration method is: injecting a sulfide solution into the cathode chamber of the electrolytic cell, so that the sulfide solution reacts with the deactivated CO2 catalytic electrode to regenerate the CO2 catalytic electrode in situ. Although this method has the same purpose as the method proposed in the present invention, the types of catalytic electrodes are different, and the ways and methods of active regeneration of the catalytic electrode are different; moreover, the CO selectivity of the catalytic electrode after in-situ regeneration with the sulfide solution is 54-66%, which is much lower than the active regeneration effect in the present invention. In the present invention, after the nanoporous Au electrode (NPG) is subjected to electrochemical redox treatment, the CO selectivity performance is improved to more than 90%, and after the nanoporous Ag electrode (NPS) is subjected to electrochemical redox treatment, the CO selectivity performance is improved to more than 85%.

Claims

1. A method for regenerating the activity of a deactivated metal catalytic electrode, characterized in that: Performing electrochemical redox treatment on the deactivated metal catalytic electrode to obtain an active regenerated metal catalytic electrode; The electrochemical redox treatment includes a cyclic voltammetric reduction method or a pulse redox followed by an electrolytic reduction method.

2. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 1, characterized in that: When the metal catalytic electrode is a nanoporous Au-Ag alloy electrode, a cyclic voltammetric reduction method is used.

3. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 2, characterized in that: In the cyclic voltammetry reduction method, the cyclic voltammetry method was first used for testing. The potential window in the cyclic voltammetry method was set to a starting potential of 0.74 V vs. RHE, a termination potential of 1.74 V vs. RHE, and a scan rate of 5 mV s -1 , scanning circle number ≥ 10 circles, completion time 4000s; Then, the Au-Ag alloy electrode is subjected to electrochemical CO2 reduction using a current-time method.

4. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 3, characterized in that: The potential of the current-time method was selected as -0.5 V vs. RHE.

5. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 1, characterized in that: When the metal catalytic electrode is a nanoporous Ag electrode, a pulse oxidation-reduction followed by electrolytic reduction method is adopted.

6. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 5, characterized in that: In the pulse oxidation-reduction followed by electrolytic reduction method, a multi-potential step method is first used to perform electrochemical oxidation to obtain a Ag oxide electrode; and then a current-time method is used to perform electrochemical CO2 reduction on the obtained Ag oxide electrode.

7. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 6, characterized in that: The parameters of the multi-potential step method were set as E1(V)=0.8V vs.RHE, T1(s)=0.01; E2(V)=2.2V vs.RHE, T2(s)=0.01, and the number of cycles was 360000 cycles; the potential of the current-time method was set as -0.8V vs.RHE, and the time was 900s.

8. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 2, characterized in that: The Au-Ag alloy electrode refers to Au 35 Ag 65 The loose porous material is prepared by the alloy strip being dealloyed or electrochemically corroded by concentrated nitric acid.

9. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 8, characterized in that: The Au 35 Ag 65 In the alloy strip, the atomic percentage content of Ag is 2.5 at.% to 5 at.%.

10. A method for regenerating the activity of a deactivated metal catalytic electrode according to claim 5, characterized in that: The nanoporous Ag electrode refers to a porous material prepared by electrochemical oxidation and reduction of Ag foil.

Citation Information

Patent Citations

  • In-situ regeneration method of electrochemical reduction CO2 catalytic electrode

    CN118048662A

Cited By

  • Fe / N / C oxygen reduction catalyst active site on-line cleaning and activating method

    CN121253637A